Capacidade para o trabalho, sintomas osteomusculares e qualidade de vida entre operadores de máquinas agrícolas - Milani, Daniela (2011)
Introduction: Studies about work ability are relevant specially due to the population aging and the workforce aging in order to avoid early retirement. Those subjects whose employment has physical demands present more frequently injuries than others. The musculoskeletal disorders are the most common disorders among these injuries. These disorders have been important cause for work ability decrease among workers and may have negative impact in their quality of life. The agricultural sector activities include tasks with important physical demands. These tasks may have a negative impact in the workers health. However in Brazil, health-related aspects of these workers are unusual. Objectives: To evaluate the work ability and its association with musculoskeletal symptoms and quality of life aspects in agricultural machinery operators. Methodology: A cross-sectional study was carried out in an industry of the sugarcane sector in Brazil. The subjects (n=204) were agricultural machinery operator. They answered a questionnaire on demographics, work, lifestyle characteristics, Work Ability Index (WAI), The Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) and the Nordic Musculoskeletal Symptoms questionnaire. Results: The mean age of the workers was 32.3 years. The men comprised 99% of the study population and the average duration of work at the institution was 5.4 years. Physical activity was reported by 45.1%. Considering at least one body part, the musculoskeletal symptoms presence over the past 12 months was reported by 47.1% of the workers and the upper back symptoms were most frequents. The SF-36 dimensions presented scores above 79.3 points and a mean WAI score was 45.2 points. The statistical analysis showed that the work ability was associated with age, education and musculoskeletal symptoms. The wrists and hands symptoms were significantly associated with work ability. Those SF-36 dimensions that had most significant with work ability were role physical and bodily pain. Conclusion: Although in this study the workers had been young, important portion have already presented musculoskeletal symptoms and presented signs of work ability reduction. Furthermore, in this study, the musculoskeletal symptoms were significantly associated with WAI reduction and due to this; it is recommended that measures about promotion and improvement of the work ability and quality of life are deployed to base in musculoskeletal disorders prevention.